1999
DOI: 10.1152/ajpcell.1999.277.2.c183
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblasts. II. Intestinal subepithelial myofibroblasts

Abstract: Intestinal subepithelial myofibroblasts (ISEMF) and the interstitial cells of Cajal are the two types of myofibroblasts identified in the intestine. Intestinal myofibroblasts are activated and proliferate in response to various growth factors, particularly the platelet-derived growth factor (PDGF) family, which includes PDGF-BB and stem cell factor (SCF), through expression of PDGF receptors and the SCF receptor c- kit. ISEMF have been shown to play important roles in the organogenesis of the intestine, and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
486
0
45

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 527 publications
(546 citation statements)
references
References 216 publications
15
486
0
45
Order By: Relevance
“…[29][30][31][32] In fact, the features of subepithelial myofibroblasts in lung adenocarcinoma are quite similar to those reported for pericryptal fibroblasts Figure 4 Subepithelial myofibroblasts in invasive lung adenocarcinomas (a-smooth muscle actin staining). In areas of central collapse and fibrosis, the myofibroblastic layer around the neoplastic acinar structure was discontinuous (a).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…[29][30][31][32] In fact, the features of subepithelial myofibroblasts in lung adenocarcinoma are quite similar to those reported for pericryptal fibroblasts Figure 4 Subepithelial myofibroblasts in invasive lung adenocarcinomas (a-smooth muscle actin staining). In areas of central collapse and fibrosis, the myofibroblastic layer around the neoplastic acinar structure was discontinuous (a).…”
Section: Discussionsupporting
confidence: 55%
“…Pericryptal fibroblasts are more abundant in adenoma than in normal colon, and gradually decrease during the progression from adenoma to intramucosal carcinoma to submucosal invasive carcinoma. [29][30][31][32] In invasive carcinomas they are virtually absent. 29 Pericryptal fibroblasts are also absent in normal gastric mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Additionally, CB2 knockout mice are more sensitive than wild-type littermates to bleomycin-induced dermal fibrosis. 35 As > 30 % of patients with Crohn ' s disease develop intestinal fibrosis leading to stricture formation, frequently requiring surgical resection, 36 and myofibroblasts are key cells in the process of wound healing and stricture formation in the gut, 37 we investigated the in vitro effects of MAEA on myofibroblasts isolated from intestinal Crohn ' s disease strictures. We found that MAEA reduced collagen production by strictured Crohn ' s disease myofibroblasts and increased their migration ability, thus supporting the view that endocannabinoid pathways might be involved in the fibrogenic process in Crohn ' s disease.…”
Section: Articlesmentioning
confidence: 99%
“…1,6,17,18 CAFs as key factors of abnormal epithelial-stromal interaction and their powerful tumor-supportive effect (eg, increased regulator ligand and extracellular matrix molecule expression) are well known compared with normal stromal cells with similar morphology, that is, subepithelial myofibroblasts. [18][19][20] Tumor cellreleased exosomes are also detectable in the circulation where the plasma level of their specific proteins (eg, CD63 and tumor susceptibility gene 101/TSG101) and miRNA content may be useful as diagnostic and/or prognostic markers in different tumor types including colorectal carcinomas. [21][22][23][24] Our study was designed to analyze the top exosome-specific markers based on change of their tissue mRNA level during colorectal adenomacarcinoma sequence.…”
mentioning
confidence: 99%